Josephine Metrics of Austrian Galicia: an Attempt to Legalize Peasant Land Ownership and Influence Socio-Economic Relations at the End of the 18th Century (On the Example of the Village of Vivsia) - Terlyuk, Ivan (Studia Historiae Oeconomicae, 2025)
This study explores the Josephine cadastre as the first systematic land registry documentation in the territory of Galicia during the late 18th century, positioning it as a legal and administrative instrument of the Habsburg Monarchy. The research aims to analyse the Josephine cadastre’s role in the regulation of legal relations between landlords and peasants within the framework of cadastral reforms, using the village of Vivsia as a microhistorical case study. The methodological framework is based on the dialectical method, enabling a comprehensive analysis of socio-political and legal processes at both the imperial and local levels. The article examines the internal structure of the cadastre, particularly the Grundbuch (land income register), and outlines the procedures of land measurement and tax calculation based on crop yields of key cereals and hay. Special attention is paid to the juridification of peasant land tenure and the formalisation of surnames as legal entities, reflecting broader socio-legal transformations in Austrian Galicia. The originality of the research lies in its application of a microhistorical approach to a single locality, which reveals the complexities of implementing imperial reforms at the village level and their unintended consequences. The study argues that while the Josephine cadastre was designed to facilitate equitable taxation and legal clarity, its practical implementation often diverged from the reformist intentions due to vested interests. Thus, the article positions the Josephinian Cadastre not only as a fiscal instrument but also as a source for understanding socio-legal transformations in Galicia.